Efficacy of an Inhibitor of Hepatitis B Virus Expression in Combination With Entecavir and Interferon‐α in Woodchucks Chronically Infected With Woodchuck Hepatitis Virus. Issue 6 (22nd April 2020) - Menne, Stephan; Wildum, Steffen; Steiner, Guido; Suresh, Manasa; Korolowicz, Kyle; Balarezo, Maria; Yon, Changsuek; Murreddu, Marta; Hong, Xupeng; Kallakury, Bhaskar V.; Tucker, Robin; Yang, Song; et al.
Abstract : RG7834 is a small‐molecule inhibitor of hepatitis B virus (HBV) gene expression that significantly reduces the levels of hepatitis B surface antigen (HBsAg) and HBV DNA in a humanized liver HBV mouse model. In the current study, we evaluated the potency of RG7834 in the woodchuck model of chronic HBV infection, alone and in combination with entecavir (ETV) and/or woodchuck interferon‐α (wIFN‐α). RG7834 reduced woodchuck hepatitis virus (WHV) surface antigen (WHsAg) by a mean of 2.57 log10 from baseline and WHV DNA by a mean of 1.71 log10 . ETV + wIFN‐α reduced WHsAg and WHV DNA by means of 2.40 log10 and 6.70 log10, respectively. The combination of RG7834, ETV, and wIFN‐α profoundly reduced WHsAg and WHV DNA levels by 5.00 log10 and 7.46 log10, respectively. However, both viral parameters rebounded to baseline after treatment was stopped and no antibody response against WHsAg was observed. Effects on viral RNAs were mainly seen with the triple combination treatment, reducing both pregenomic RNA (pgRNA) and WHsAg RNA, whereas RG7834 mainly reduced WHsAg RNA and ETV mainly affected pgRNA. When WHsAg was reduced by the triple combination, peripheral blood mononuclear cells (PBMCs) proliferated significantly in response to viral antigens, but the cellular response was diminished after WHsAg returned to baseline levels during the off‐treatment period. Consistent with this, Pearson correlation revealed a strong negative correlation between WHsAg levels and PBMC proliferation in response to peptides covering the entire WHsAg and WHV nucleocapsid antigen. Conclusion: A fast and robust reduction of WHsAg by combination therapy reduced WHV‐specific immune dysfunction in the periphery. However, the magnitude and/or duration of the induced cellular response were not sufficient to achieve a sustained antiviral response.